Zatoichi and the Chess Expert Based on a Short Story by Kan Shimozawa - Misumi, Kenji; Makiura, Chishi; Katsu, Shintaro; Narita, Mikio; Hayashi, Chizu (Zatoichi: The Blind Swordsman Collection, 2019)
Kenji Misumi, who directed the first installment of the Zatoichi series, returns with this tale in which the blind swordsman once again finds himself the protector of a child: a little girl pursued by both devious family members and bloodthirsty ruffians. Further complicating his journey is a new acquaintance - a tremendously skilled chess player (the charismatic Mikio Narita) who has mysterious motivations and a dark past. [www.criterion.com]